Penggunaan Strategi Problem Based Learning dalam Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Kelas 2 SD - Kamilatus Sakinah; Deviana Ramadhani; Moh. Dany Marta; Nur Wiji Sholikin (IEC: Journal of Educational Innovation, 2026)
Mathematical problem solving skills are one of the key competencies that need to be developed starting in elementary school, as they play a role in enhancing students’ logical, critical, and creative thinking abilities. However, in reality, many students still struggle with solving math problems, particularly those involving contextual problems. This situation highlights the need to implement learning strategies that actively engage students in the learning process. This study aims to determine the effect of using the Problem Based Learning (PBL) strategy on improving the mathematical problem solving skills of second grade elementary school students. The research method used is quantitative research with a pre-experimental design employing a one-group pretest posttest design. The research subjects were second grade elementary school students selected using purposive sampling. Data collection was conducted through mathematics problem-solving ability tests administered before and after the implementation of the PBL strategy. The data were analyzed using descriptive statistics and hypothesis testing to determine the differences in students’ abilities before and after the intervention. The results of the study indicate that the implementation of the Problem Based Learning strategy significantly improved students’ mathematics problem-solving abilities. Thus, the Problem Based Learning strategy can serve as an effective alternative learning method to improv.